Selected Abstracts of the 4th International Congress of UENPS; Athens (Greece); December 11th-14th 2014 - - (Hygeia Press di Corridori Marinella, 2014)
Selected Abstracts of the 4th International Congress of UENPS • Athens (Greece) • December 11th-14th 2014 The Congress has been organized by the Union of European Neonatal and Perinatal Societies (UENPS). Guest Editor: Giuseppe Buonocore   ABS 1. COMPARISON OF PRENATAL CARE AND PREGNANCY RELATED MATERNAL RISK FACTORS BETWEEN WOMEN WHOSE BABIES ARE ADMITTED OR NOT ADMITTED TO NEONATAL INTENSIVE CARE UNIT • S.M. Avci, M. Çöl, Y. Genç, E.A. Yilmaz, Ç. Gulumser; Ankara (Turkey) ABS 2. APPEARANCE AND DISTRIBUTION OF GENES AND GENE PROTEINS IN CLEFT AFFECTED TISSUE • M. Pilmane, I. Akota; Riga (Latvia) ABS 3. MANAGEMENT OF PARENTAL STRESS IN A NEONATAL INTENSIVE CARE UNIT. A RANDOMIZED CONTROL TRIAL • A. Fotiou, K. Papagaroufalis, G. Bakoyannis, C. Bakoula; Athens (Greece) and Indianapolis (IN, USA) ABS 4. A CASE OF LARYNGEAL ATRESIA ACCOMPANIED BY PERSISTENT PHARYNGOTRACHEAL DUCTUS IN NEWBORN • L. Korkmaz, I. Guneş, H. Halis, I. Ketenci, O. Baştuğ, M.S. Doğan; Kayseri (Turkey) ABS 5. DIFFERENTIAL REGULATION OF IRISIN AT THE EXTREMES OF FETAL GROWTH • D.D. Briana, S. Baka, M. Boutsikou, Th. Boutsikou, A. Marmarinos, D. Hassiakos, D. Gourgiotis, A. Malamitsi-Puchner; Athens (Greece) ABS 6. COPEPTIN UPREGULATION IN EARLY HUMAN MILK: POSSIBLE ROLE IN POSTNATAL ADAPTATION • D.D. Briana, Th. Boutsikou, M. Boutsikou, S. Baka, D. Piatopoulou, D. Hassiakos, D. Gourgiotis, A. Malamitsi-Puchner; Athens (Greece) ABS 7. ADROPIN ABUNDANCE IN BREAST MILK: RELATION TO MATERNAL SERUM CONCENTRATIONS AND PERINATAL FACTORS • D.D. Briana, Th. Boutsikou, M. Boutsikou, S. Baka, A. Ristani, D. Hassiakos, D. Gourgiotis, A. Malamitsi-Puchner; Athens (Greece) ABS 8. INFECTIVE ENDOCARDITIS IN NON-CATHETERISED PRETERM NEWBORN • K. Demova, F. Bauer; Nove Zamky (Slovakia) ABS 9. INCIDENCE AND RISK FACTORS FOR RETINOPATHY OF PREMATURITY • L. Banjac, S. Borovic, D. Dakić, G. Banjac; Podgorica (Montenegro) ABS 10. CASE REPORT OF NEWBORN WITH CUTIS MARMORATA TELANGIECTASICA CONGENITA • Ch. Spanoudaki, M. Lykogeorgou, N. Gezerli, V. Delivoria; Athens (Greece) ABS 11. THIRTY-FIVE YEARS OF EXPERIENCE IN A PRIVATE NICU IN GREECE • M. Saklamaki-Kontos, K. Stafylakis, M. Daniilidou, A. Thomas, I. Kontogianni; Athens (Greece) ABS 12. DYNAMICS OF DEVELOPMENTAL OUTCOMES IN VERY LOW BIRTH WEIGHT PREMATURE INFANTS IN RUSSIAN FEDERATION FROM 2003 TO 2013 • E. Sakharova, E. Keshishian, G. Alyamovskaya; Moscow (Russian Federation) ABS 13. POSTDISCHARGE FORMULA FEEDING AND DEVELOPMENTAL OUTCOMES AT 12 MONTHS OF LIFE IN VERY LOW BIRTH WEIGHT PREMATURE INFANTS • G. Alyamovskaya, E. Keshishian, E. Sakharova; Moscow (Russian Federation) ABS 14. HYPOXIC-ISCHEMIC ENTEROCOLITIS (HIEnt): A PROPOSAL FOR THE DEFINITION OF EARLY NEC AND ITS SEROLOGICAL EVIDENCE • O. Surmeli-Onay, A. Korkmaz, S. Yigit, M. Yurdakok; Ankara (Turkey) ABS 15. CHANGES IN THE PREVALENCE OF CONGENITAL DEVELOPMENTAL ABNORMALITIES IN LITHUANIA BETWEEN 2002 AND 2011 • D. Stoniene, R. Tameliene, E. Vaitkute; Kaunas (Lithuania) ABS 16. MATERNAL FAT MASS, ANTENATAL STEROIDS AND RESPIRATORY DISTRESS SYNDROME: COMPLEX RELATIONS • H.T. Çelik, A. Korkmaz, Ş. Yiğit, M. Yurdakök; Ankara (Turkey) ABS 17. INCIDENCE OF RETINOPATHY OF PREMATURITY IN PREMATURE WITH VERY LOW WEIGHT IN A GENERAL HOSPITAL IN SÃO JOSÉ DOS CAMPOS, BETWEEN 2010 AND 2013 • A.M. Puppio Querido; São José dos Campos (Brazil) ABS 18. DETERMINANTS OF LOW WEIGHT (< 3‰) IN PREMATURE INFANTS (< 32 WEEKS OF GESTATION) • R. Tamelienė, J. Garčinskienė, V. Šnipaitis, D. Stonienė; Kaunas (Lithuania) ABS 19. QUANTIFIED OXYGENATION IMPAIRMENT ACCORDING TO CATEGORIES OF SEVERITY IN BRONCHOPULMONARY DYSPLASIA • A. Davis, R. Ross-Russell, T. Dassios; Cambridge (UK) ABS 20. PLACENTAL INFARCTION IS ASSOCIATED WITH CEREBRAL PALSY: A PROSPECTIVE COHORT STUDY • M-T. Vinnars, B. Vollmer, J. Nasiell, N. Papadogiannakis, M. Westgren; Stockholm and Ornskoldsvik (Sweden) ABS 21. THE VARIABILITY IN CYSTATIN C REFERENCE VALUES IN NEONATES CAN PARTLY BE EXPLAINED BY THE USED ASSAY (TURBI- VS NEPHELOMETRY) • K. Allegaert, A. Raaijmakers, J. van den Anker, D. Mekahli, E. Levtchenko, J. vande Walle; Leuven and Ghent (Belgium), Washington (DC, USA), Rotterdam (the Netherlands), Basel (Switzerland) ABS 22. RESPIRATORY DISORDERS AND CONSEQUENT MORBIDITY OF THE "LATE PRETERM" INFANTS (GESTATIONAL AGE: 34-36+6 WEEKS) • G. Mitsiakos, K. Tsepis, E. Gkiougki, A.E. Papathanasiou, E. Lazaridou, A. Georgiadou, I. Chatzioannidis; Thessaloniki (Greece) and Liege (Belgium) ABS 23. ASYNCHRONOUS CHEST COMPRESSIONS vs SYNCHRONOUS IMPROVE 2-HOUR SURVIVAL IN AN EXPERIMENTAL NEONATAL PIGLET MODEL OF ASPHYXIAL CARDIAC ARREST • N. Iacovidou, A. Aggelina, A. Papalois, P. Pliatsika, A. Douvanas, G. Gkiokas, T. Xanthos; Athens (Greece) ABS 24. HISTORY OF BREASTFEEDING • M. Papastavrou, S. Genitsaridi, E. Komodiki, S. Paliatsou S, A. Kontogeorgou, N. Iacovidou; Athens (Greece) ABS 25. BREASTFEEDING IN PUBLIC • E. Komodiki, A. Kontogeorgou, M. Papastavrou, P. Volaki, S. Genitsaridi, N. Iacovidou; Athens (Greece) ABS 26. SURVEILLANCE OF NEONATAL SEPSIS INCIDENCE IN A PRIVATE NICU IN ATHENS, GREECE • M. Saklamaki-Kontos, P. Boka, C. Neri, A. Sideris, H. Kallimorou, M. Safiolea, V. Syriopoulou; Athens (Greece) ABS 27. LEAD AND MERCURY LEVELS IN PRETERM INFANTS BEFORE AND AFTER BLOOD TRANSFUSIONS • S. Takci, S. Yigit, A. Asci, P. Erkekoglu, A. Korkmaz-Toygar, B. Kocer-Gumusel, M. Yurdakok; Ankara (Turkey) ABS 28. THE OBSTETRICIAN AND PEDIATRICIAN BEFORE COURT: A CRITICAL CASE STUDY ON (SUB)STANDARD PERINATAL CARE • M. Eggermont; Ghent (Belgium) ABS 29. THE EFFECT OF MELATONIN TREATMENT ON OXIDANT STATUS, ANTIOXIDANT CAPACITY, LIPID PEROXIDATION AND APOPTOSIS AFTER HYPOXIC ISCHEMIC BRAIN INJURY IN NEWBORN RATS • H. Yapicioglu Yildizdas, B. Mutlu, S. Erdogan, S. Zorludemir, F. Ozlu, M. Satar, N. Narli; Adana (Turkey) ABS 30. GROWTH OF PRETERM NEONATES WITH BRONCHOPULMONARY DYSPLASIA AND ITS LONG TERM IMPLICATIONS IN RESPIRATORY FUNCTION • A. Gounaris, R. Sokou, P. Panagiotounakou, D. Bleco, M. Papadopoulou, J. Labadaridis; Larissa, Piraeus and Athens (Greece) ABS 31. THE SIGNIFICANCE OF UMBILICAL ARTERY BLOOD PH, BASE DEFICIT, BICARBONATE, AND LACTATE LEVELS FOR RESUSCITATION NEEDS IN FULL-TERM NEONATES, THEIR CEREBRAL BLOOD CIRCULATION CHANGES, AND HYPOXIC-ISCHEMIC ENCEPHALOPATHY • A. Kudreviciene, A. Basevicius, S. Lukosevicius, J. Laurynaitiene, R. Tameliene; Kaunas (Lithuania) ABS 32. GROSS MOTOR PATHS IN GREEK "HEALTHY" PRETERM INFANTS ASSESSED BY THE ALBERTA INFANT MOTOR SCALE (AIMS): COMPARISON WITH FULL-TERM INFANTS AND INFLUENCE OF NEONATAL MORBIDITY FACTORS • D. Syrengelas, V. Kalampoki, P. Kleisiouni, V. Manta, S. Mellos, T. Siahanidou; Athens (Greece) ABS 33. PERINATAL OUTCOME IN PREGNANT WOMEN WITH GESTATIONAL AND OVERT DIABETES AND ACCORDING TO WHO AND/OR IADPSG CRITERIA • J. Djelmis, M. Ivanisevic, M. Pavic; Zagreb (Croatia) ABS 34. SURVIVAL AND NEONATAL COMPLICATIONS IN EXTREMELY PREMATURE NEONATES 22+0-27+0 WEEKS OF GESTATION. COMPARISON OF TWO TIME PERIODS • I. Nikaina, M. Taliadourou, I. Stavrakas, G. Liosis, M. Tzaki; Athens (Greece) ABS 35. NEONATAL CREATINEMIA TRENDS IN RELATION TO BAYLEY SCALES OF INFANT DEVELOPMENT® IN FORMER EXTREMELY LOW BIRTH WEIGHT (ELBW) NEONATES • A. Raaijmakers, E. Ortibus, T.P. van Tienoven, C. Vanhole, E. Levtchenko, K. Allegaert; Leuven and Brussels (Belgium) ABS 36. IS A SMALL PLATELET MASS ASSOCIATED WITH INTRAVENTRICULAR HEMORRHAGE IN EXTREMELY LOW BIRTH WEIGHT INFANTS? • G. Mitsiakos, E. Chatziioannidis, K. Tsepis, A.E. Papathanasiou, I. Dorka, E. Lazaridou, N. Nikolaidis; Thessaloniki (Greece) ABS 37. A CASE OF SEVERE HEMOLYTIC DISEASE OF NEWBORN CAUSED BY ALLOANTIBODIES AGAINST ANTIGENS D AND E TO THE SYSTEM RHESUS TREATED WITH INTRAUTERINE TRANSFUSIONS AND EX-UTERO EXCHANGE TRANSFUSIONS • G. Mitsiakos, E. Babatseva, B. Papageorgiou, I. Chatziioannidis, K. Tsepis, A. Athanasiadis, A. Kioumi, N. Nikolaidis; Thessaloniki (Greece) ABS 38. EVALUATION OF SERUM HEPCIDIN LEVELS AND HEMATOLOGICAL PARAMETERS IN PRETERM INFANTS BEFORE AND AFTER THE TRANSFUSION OF PACKED RED BLOOD CELLS • F. Stripeli1, J. Kapetanakis, D. Gourgiotis, T. Anastasiou, L. Kossiva; Athens (Greece) ABS 39. PLATELET MASS IN PRETERM INFANTS OF PREECLAMPTIC MOTHERS AND ASSOCIATION WITH NEONATAL MORBIDITIES • D. Anuk-Ince, S. Takcı, R. Gumuser, B.